STUDIES ABOUT THE KEY ELEMENTS OF TOTAL QUALITY MANAGEMENT - Milosan, Ioan (European Scientific Journal, ESJ, 2014)
Total Quality Management is an organizational strategy founded on the idea that performance in achieving a quality education is achieved only through involvement with the perseverance of the entire organization in improving processes permanently. The objective is to increase the efficiency and effectiveness in satisfying the customers. The paper presents some fundamentals aspects about the Total Quality Management (TQM) concept and it is pointed out the 6 key elements for successfully implemented TQM organization: Confidence, Training, Teamwork, Leadership, Recognition and Communication.